Combining immunotherapy with transarterial radioembolization - (:unkn) unknown (My University, 2023)
Hepatocellular carcinoma (HCC) has a high mortality rate due to the diagnosis of patients at advanced stages and ineffective systemic therapies. Immunotherapy is considered a new treatment option for unresectable HCC alternatives to the limitations of conventional cytotoxic chemotherapy. In this case report, we reported that transarterial radioembolization and immunotherapy such as atezolizumab and bevacizumab can be used together in a manner effectively in the management of HCC treatment.
Keywords: Tıp; Dahili Tıp Bilimleri; Nükleer Tıp; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Nuclear medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; RADYOLOJİ, NÜKLEER TIP ve MEDİKAL GÖRÜNTÜLEME; Clinical Medicine (MED); CLINICAL MEDICINE; RADIOLOGY, NUCLEAR MEDICINE & MEDICAL IMAGING; Radyoloji, Nükleer Tıp ve Görüntüleme; Radiology, Nuclear Medicine and Imaging; Atezolizumab; fluorodeoxyglucose positron emission tomography-computed tomography; hepatocellular carcinoma transarterial radioembolization; Atezolizumab; fluorodeoxyglucose positron emission tomography‑computed tomography; hepatocellular carcinoma; transarterial radioembolization